KAJIAN HUKUM TERHADAP PUTUSAN PENGADILAN NEGERI TOBELO NOMOR: 15/PID.SUS/2016/PN.TOB TENTANG DELIK PERCOBAAN PERSETUBUHAN TERHADAP ANAK - Selfianus Laritmas (Jurnal Akrab Juara, 2019)
Crime of Trial Against Children can be punished if the commencement of implementation is real, Criminal acts of sexual abuse are generally acts or acts that violate decency that intentionally damage politeness. The threat of criminal offenses for underage children according to Article 82 of Law No.23 of 2002 concerning Child Protection is punishable by imprisonment of a maximum of 15 (fifteen) years and a minimum of 3 (three) years and a maximum fine of Rp.300,000,000. 00 (three hundred million rupiah) and at least Rp. 60,000,000.00 (sixty million rupiahs). Based on the results of the research and discussion of the decision Number: 15 / pid.sus / 2016 / PN.Tob. Against a child and sentenced to 5 years in prison. The problem is that the defendant in carrying out his actions did not commit acts of immorality as referred to in Article 81 of Law No. 35 of 2014, Jo Article 53 of the Criminal Code so that when viewed from the point of view of justice it is very unfair because the sentence imposed is not in accordance with what was done